2017
DOI: 10.1038/s41598-017-06310-z
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Genetic Interaction Between Irf6 and Twist1 during Craniofacial Development

Abstract: Interferon Regulatory Factor 6 (IRF6) and TWIST1 are transcription factors necessary for craniofacial development. Human genetic studies showed that mutations in IRF6 lead to cleft lip and palate and mandibular abnormalities. In the mouse, we found that loss of Irf6 causes craniosynostosis and mandibular hypoplasia. Similarly, mutations in TWIST1 cause craniosynostosis, mandibular hypoplasia and cleft palate. Based on this phenotypic overlap, we asked if Irf6 and Twist1 interact genetically during craniofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Previous studies had focused on the importance of IRF6 in epithelial cells and wound healing due to the obvious pathologies observed in VWS and PPS patients at birth (Ingraham et al, ; Vieira, ; Letra et al, ; Fakhouri et al, ; Joly et al, ), though this study concentrated on the effect of IRF6 on craniofacial bone formation due to aberrant skeletal phenotype observed in Irf6 ‐null mice (Ingraham et al, ) and dominant negative Irf6 in Zebrafish (Duncan et al, ). Although our previous study suggested an intercellular role of IRF6, which is highly expressed in epithelial cells on mandibular bone development (Fakhouri et al, ), no studies thus far have investigated whether IRF6 is involved in regulating bone and cartilage development in a cell‐autonomous manner. Interestingly, our finding of IHC staining extended the knowledge about the current perception of IRF6’s role in intramembranous bone formation by reporting the distinct expression in intramembranous‐differentiated osteogenic cells, as well as in hypertrophic chondrocytes of Meckel's and nasal cartilage.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies had focused on the importance of IRF6 in epithelial cells and wound healing due to the obvious pathologies observed in VWS and PPS patients at birth (Ingraham et al, ; Vieira, ; Letra et al, ; Fakhouri et al, ; Joly et al, ), though this study concentrated on the effect of IRF6 on craniofacial bone formation due to aberrant skeletal phenotype observed in Irf6 ‐null mice (Ingraham et al, ) and dominant negative Irf6 in Zebrafish (Duncan et al, ). Although our previous study suggested an intercellular role of IRF6, which is highly expressed in epithelial cells on mandibular bone development (Fakhouri et al, ), no studies thus far have investigated whether IRF6 is involved in regulating bone and cartilage development in a cell‐autonomous manner. Interestingly, our finding of IHC staining extended the knowledge about the current perception of IRF6’s role in intramembranous bone formation by reporting the distinct expression in intramembranous‐differentiated osteogenic cells, as well as in hypertrophic chondrocytes of Meckel's and nasal cartilage.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, syngnathia and rib abnormalities have been reported in severe cases of PPS (Escobar and Weaver, ; Cardoso et al, ; Vandeweyer et al, ). Similarly, a complete loss of Irf6 in mice leads to skeletal abnormalities, including xiphoid and digit malformation (Ingraham et al, ; Fakhouri et al, ), while exogenous overexpression of IRF6 in basal epithelium partly rescued the craniofacial phenotype in Irf6 null embryos (Kousa et al, ). Despite all these findings, no studies have reported IRF6 expression in osteogenic cells during bone formation (Fakhouri et al, ; Manocha et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to IRF6 , the TWIST1 gene regulates neural tube closure during embryonic development and cranial suture fusion during skull development. Mutations in TWIST1 can cause craniosynostosis, mandibular hypoplasia, and cleft palate (Fakhouri et al ., 2017). Inhibition or alteration of IRF6 and TWIST1 expression can be done similar to the methods performed by Miettinen et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, difficulties arise in in vivo experiments when the study begins to incorporate genetic interactions and rescue experiments of two or more allelic mutations. In our recent study, the genetic interaction between Irf6 and Twist1 causes severe mandible abnormality and cleft of the secondary palate in the mouse model (Fakhouri et al ., 2017). …”
Section: Introductionmentioning
confidence: 99%